2017
DOI: 10.1002/asia.201701215
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Assisted Design of Imidazolate‐Based Ionic Liquids for Improving Sulfur Dioxide Capture, Carbon Dioxide Capture, and Sulfur Dioxide/Carbon Dioxide Selectivity

Abstract: A new strategy involving the computer-assisted design of substituted imidazolate-based ionic liquids (ILs) through tuning the absorption enthalpy as well as the basicity of the ILs to improve SO capture, CO capture, and SO /CO selectivity was explored. The best substituted imidazolate-based ILs as absorbents for different applications were first predicted. During absorption, high SO capacities up to ≈5.3 and 2.4 molSO2  mol could be achieved by ILs with the methylimidazolate anions under 1.0 and 0.1 bar (1 bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…The total Δ H values of primary and secondary amines on [DETAH] + reacted with CO 2 were −80.32 and −76.63 kJ·mol –1 , respectively. A higher negative value of Δ H led to a stronger interaction between amine and CO 2 . It seemed that the primary amino group on [DATAH] + would have prior and faster reaction with CO 2 compared with the secondary amino group on [DATAH] + .…”
Section: Resultsmentioning
confidence: 99%
“…The total Δ H values of primary and secondary amines on [DETAH] + reacted with CO 2 were −80.32 and −76.63 kJ·mol –1 , respectively. A higher negative value of Δ H led to a stronger interaction between amine and CO 2 . It seemed that the primary amino group on [DATAH] + would have prior and faster reaction with CO 2 compared with the secondary amino group on [DATAH] + .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the unique chemical and physical properties, functionalized ionic liquids (ILs) with active sites on their cations or anions as a kind of alternative absorbent result in efficient gas capture. , For example, functionalized ILs with amine-containing cations, ether-containing cations, aprotic heterocyclic anions, cyano-containing anions, , carbonyl-containing anion, carboxylate anions, and phenolate anions have been designed and synthesized for improving SO 2 or CO 2 capture. These functionalized ILs are usually prepared through complicated processes, including cationization, anion-exchange, and acid–base neutralization, with kinds of organic solvents used and large quantities of wastewater produced which may enhance their cost and limit their large-scale applications. , …”
Section: Introductionmentioning
confidence: 99%
“…It was found that SO 2 absorption capacities in EmimCl-Im (2:1) decrease with the increasing content of water, affording a SO 2 absorption capacity of 1.178 g SO 2 per g DES when EmimCl-Im (2:1) contains 10 wt % water (Figure b). By comparing the SO 2 gravimetric absorption capacities with previously reported ILs or DESs, these bisazole-based DESs exhibit higher SO 2 absorption (Table S4). As a result, the bisazole-based DESs are highly efficient SO 2 absorbers.…”
Section: Resultsmentioning
confidence: 80%